2014
DOI: 10.1098/rsfs.2014.0004
|View full text |Cite
|
Sign up to set email alerts
|

Computational modelling of the inflammatory response in trauma, sepsis and wound healing: implications for modelling resilience

Abstract: Resilience refers to the ability to recover from illness or adversity. At the cell, tissue, organ and whole-organism levels, the response to perturbations such as infections and injury involves the acute inflammatory response, which in turn is connected to and controlled by changes in physiology across all organ systems. When coordinated properly, inflammation can lead to the clearance of infection and healing of damaged tissues. However, when either overly or insufficiently robust, inflammation can drive furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…We focused on HMGB1 as a proximal mediator of interest because of its known role as a driver of inflammation in models of APAP-induced liver injury 7 . As an extension of our previous work 8,9 , Translational Systems Biology modeling methodology developed for biologically complex and dynamic conditions 10,11 was applied to correlate biomarkers with clinical outcomes as well as identify potential therapeutic targets in PALF. Recapitulation of these findings using an in vitro model of isolated HC exposed to APAP ± NAC was used to create a bedside-to-bench translational platform for further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…We focused on HMGB1 as a proximal mediator of interest because of its known role as a driver of inflammation in models of APAP-induced liver injury 7 . As an extension of our previous work 8,9 , Translational Systems Biology modeling methodology developed for biologically complex and dynamic conditions 10,11 was applied to correlate biomarkers with clinical outcomes as well as identify potential therapeutic targets in PALF. Recapitulation of these findings using an in vitro model of isolated HC exposed to APAP ± NAC was used to create a bedside-to-bench translational platform for further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of the fundamental quantity F in Equation (1) via the control and output variables u and y will be detailed in Section 2.2. It connects our approach to the data-driven viewpoint which has been adopted in control engineering (see, e.g., [39,42,67,68]) and in studies about inflammation (see, e.g., [9,20,69,84]).…”
Section: Remarkmentioning
confidence: 99%
“…Sepsis in an inflammatory condition with a mortality rate of between 28%-50% (1). Numerous mechanistic computational simulations of acute inflammation and sepsis have been utilized over the past two decades (2)(3)(4)(5)(6)(7)(8)(9). These models have demonstrated that the sepsis population is much more heterogeneous than previously thought and this can be reflected by utilizing a range of multidimensional parameters that correlate to biologically plausible behaviors and phenotypes.…”
Section: Introductionmentioning
confidence: 99%